Effect of Sr surface segregation of La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 − δ electrode on its electrochemical performance in SOC - Pan, Zehua (2019)
The degradation mechanism of La0.6Sr0.4Co0.2Fe0.8O3 − δ (LSCF) electrode is investigated by examining its electrochemical behavior under equilibrium potential at elevated temperature and corresponding surface compositional changes. Diluted nitric acid etching treatment is conducted to confirm the correlation between the surface changes and the variation of electrochemical performance. It has been shown that the increase of polarization resistance of LSCF electrode has a linear dependence on the square root of time and arises from degradation of mass transfer process taking place at the gas-solid interface of electrode, such as oxygen adsorption/desorption and surface diffusion. Comparison of the behavior of the electrode before and after nitric acid treatment shows that the presence of surface inhibited species can account for the above observations. This inhibited species is confirmed by X-ray photoelectron spectroscopy to be a surface segregated Sr-based material, which supports the claim that surface Sr segregation is detrimental. A further lifespan study of LSCF electrode up to 158 h under 1 A/cm2 electrolysis current demonstrates that the current can improve and stabilize the performance, which could be ascribed to the removal of surface Sr species due to the incorporation of surface Sr back into the lattice of LSCF.